Skip to main content

Advertisement

Table 3 Transformation rules for τ (for targets) and π (for policies) for decision 0

From: A framework for the extended evaluation of ABAC policies

τ0((a,v)) = \(\neg a_{v} \wedge \bigvee \{ a_{v^{\prime }} \mid v^{\prime }\in \mathcal {V}_{\mathcal {A}}\}\)
τ0t1) = τ1(t1)
\(\tau _{0}(\mathop {\sim } t_{1})\) = τ0(t1)τ(t1)
τ0(E1(t1)) = τ0(t1)
τ0(t1 t2) = τ0(t1)τ0(t2)
τ0(t1t2) = (τ0(t1)¬τ(t2))(τ0(t2)¬τ(t1))
\(\tau _{0}(t_{1} \mathbin {\vartriangle } t_{2})\) = τ0(t1)τ0(t2)
τ0(t1 t2) = τ0(t1)τ0(t2)
τ0(t1t2) = τ0(t1)τ0(t2)
\(\tau _{0}(t_{1} \triangledown t_{2})\) = (τ0(t1)¬τ1(t2))(τ0(t2)¬τ1(t1))
π0(1) = false
π0(0) = true
π0((t,p1)) = τ1(t)π0(p1)
π0p1) = π1(p1)
\(\pi _{0}(\mathop {\sim } p_{1})\) = π0(p1)π(p1)
π0(E1(p1)) = π0(p1)
π0(p1 p2) = π0(p1)π0(p2)
π0(p1p2) = (π0(p1)¬π(p2))(π0(p2)¬π(p1))
\(\pi _{0}(p_{1} \mathbin {\vartriangle } p_{2})\) = π0(p1)π0(p2)
π0(p1 p2) = π0(p1)π0(2)
π0(p1p2) = π0(p1)π0(p2)
\(\pi _{0}(p_{1} \triangledown p_{2})\) = (π0(p1)¬π1(p2))(π0(p2)¬π1(p1))